Chimeric CTLA4-CD28-CD3z T Cells Potentiate Antitumor Activity Against CD80/CD86–Positive B Cell Malignancies - Lin, Shouheng; Cheng, Lin; Ye, Wei; Li, Shanglin; Zheng, Diwei; Qin, Le; Wu, Qiting; Long, Youguo; Lin, Simiao; Wang, Suna; Huang, Guohua; Li, Peng; et al. (Frontiers in Immunology, 2021)
The adoptive transfer of chimeric antigen receptor T (CAR T) cells have been recognized as a promising therapeutic strategy for the treatment of hematological malignancies; however, clinical success using CAR T cells for the treatment of solid tumors are still limited since the T-cell function is inhibited by negative signals in the microenvironment of solid tumors. CTLA4 is a well-known immune checkpoint molecule, thus we developed a novel CAR by converting this negative signal to positive signal. The CAR developed consists of the extracellular and transmembrane domains of CTLA4 and the cytoplasmic domains of CD28 and CD3z (CTLA4-CAR T). CTLA4-CAR T cells exhibited superior cytokine secreting activities and cytotoxic to tumor cells in vitro and in xenograft models. CTLA4-CAR T cells were found to accumulate in tumors and are toxic to Myeloid-derived suppressor cells (MDSCs) without signs of severe GVHD and CRS in preclinical models. Thus, this chimeric CTLA4-CAR can enhance the antitumor activity of CAR T cells, and shed light on the strategy of using armed CAR T cells to target the immunomodulatory tumor microenvironment.